Implementasi Konfigurasi Jaringan Dalam Supply Chain Management Pada Mitra Usaha Es Teh Nusantara yang Berada di Kota Metro - Deviana, Lisa; Refianti, Alya; Fauziyah, Nurul; Mellinda F., Chintya; Anatasya, Fera (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the configuration of supply chain management (SCM) in Es Teh Nusantara in Metro City, focusing on operational efficiency and its impact on customer satisfaction. Es Teh Nusantara, as a ready-to-eat beverage company, faces challenges in managing an effective supply chain to reduce costs, accelerate distribution, and maintain product quality. Through a qualitative descriptive approach, data was collected through field observations, interviews with management and business partners, and analysis of related documents. The results of the study show that the network structure of Es Teh Nusantara involves raw material suppliers, factories, storage warehouses, distributors, and business partners. The selection of strategic locations for factories and warehouses has succeeded in reducing transportation costs and raw material procurement time. An efficient distribution system allows for fast and timely delivery of products. Operational efficiency is achieved through the management of cost, time, and maintained product quality, which in turn improves customer satisfaction. However, the study also found challenges related to fluctuations in market demand and suboptimal distribution coordination at a time when demand is increasing rapidly. This research provides several important benefits and contributions to Es Teh Nusantara and the ready-to-eat beverage industry, as well as enriching the literature in the field of supply chain management.